Patterns of Malignancies in a Tertiary Health Facility in Benue State, North-Central Nigeria: A Three-year Retrospective Analysis, 2023–2025 - Otache Adah Emmanuel; Agida E. Teddy; Rose Abah; Ntat Charles Ibiok; Emmanuel Amaechi Nwobi; Ocheifa Ngbede Matthew; Ogwuche Austin Opiih; Chuhwak Sally Judith; Enye Agada; Onyewuchi Amina Japhet; Bamidele Israel Omolabake; Anejo-Okopi Joseph (SAR Journal of Medicine, 2026)
Background: Cancer is an expanding cause of morbidity and mortality worldwide, with a growing share of the burden occurring in low- and middle-income countries. In sub-Saharan Africa, deficiencies in population-based registration, pathology, imaging, screening, and treatment access continue to limit cancer control. Hospital-based data, while not population-representative, remain useful for characterizing local service demand and identifying priority cancer types. Objective: To describe the demographic and site-specific pattern of malignancies and factors associated with female cancer presentation at the Federal University of Health Sciences Teaching Hospital (FUHSTHO), Otukpo, Benue State, Nigeria, from January 2023 to December 2025. Methods: This three-year retrospective hospital-based descriptive study included histologically confirmed malignancies and clinically diagnosed malignancies supported by radiological evidence where histology was unavailable. Cancer records were identified from the Hospital Cancer Registry and Medical Records Department using ICD-10 codes C00–C97. Age, sex, residence, and primary cancer site were extracted. Categorical variables were summarized using frequencies, percentages, and 95% confidence intervals. Binary logistic regression was used to examine demographic factors associated with female cancer presentation. Analyses were performed in IBM SPSS Statistics version 26. Results: Of 160 cancer records identified, 145 were eligible for analysis after exclusion of 5 duplicate and 10 incomplete records. Females accounted for 91 cases (62.8%) and males for 54 (37.2%), giving a female-to-male ratio of 1.7:1. Most cases occurred among adults aged 35–64 years (87/145; 60.0%), followed by those aged ≥65 years (40/145; 27.6%). Among males, prostate cancer was the leading recorded malignancy (16/54; 29.6%), followed by lung cancer (5/54; 9.3%) and acute myeloid leukemia (4/54; 7.4%). Among females, breast cancer (33/91; 36.3%) and cervical cancer (17/91; 18.7%) together accounted for 55.0% of female cases. In adjusted analysis, age 35–64 years (AOR 3.46; 95% CI 1.52–7.88; p=0.003) and residence in Otukpo LGA (AOR 2.14; 95% CI 1.12–4.09; p=0.021) were associated with female cancer presentation; the estimate for age ≥65 years was of borderline statistical significance (AOR 2.41; 95% CI 0.99–5.84; p=0.051). Conclusion: The hospital cancer case mix was dominated by breast and cervical cancers among females and prostate cancer among males, with most cases occurring in middle-aged and older adults. These findings support strengthened cancer registration, evidence-based early detection, diagnostic capacity, and oncology referral pathways. Because the study is hospital-based, the results should not be interpreted as population incidence or prevalence estimates for Benue State.